Ways to Reduce the Resistance Torque During the Disk Rotor Spinning and to Increase the Electromotive Force in the Transverse Magnetic Flux Generator in No-Load Mode - Yehorov A.V.; Duniev O.O.; Masliennikov A.M.; Stamann M. (Problems of the Regional Energetics)
The article reviews the transverse magnetic flux machine designs. The work aim was the analysis of the transverse magnetic flux generator with a disk rotor, the stator poles optimal number selection and the resistance torque reducing. This resistance torque was created by one-sided magnetic attraction force from the permanent magnets on the rotor and it hasn’t been considered previously, which is a novelty of this work. The ways to increase the electromotive force in the generator are also considered. The main work goal was obtained by magnetic system analysis of generator using Ansys Maxwell software and disk rotor strength analysis using ASCON Компас-3D software. It is concluded that the magnetic reversal frequency of the stator cores depends on the number of permanent magnets on the rotor. The dependence of the magnetic induction average value in the U-shaped stator core on their number was obtained during the magnetic analysis. The disk rotor strength simulation allowed getting the maximum possible bend of the disk rotor under the influence of the one-sided magnetic attraction force. The neodymium permanent magnets help to improve generator efficiency and to decrease its mass-dimensional indicators. It was proposed to use an uneven permanent magnets distribution on the rotor in the transverse magnetic flux generator to reduce the resistance torque of the disk rotor. The permanent magnets attraction force that interacts with stator steel poles was considered. The dependence of magnetic attraction force of the permanent magnets on the air gap size of the generator has been obtained.